Isotretinoin-Induced Delusional Disorder, Somatic Subtype - Katharine V. Jensen; Adam Abba-Aji (Case Reports in Dermatological Medicine)
Isotretinoin, an active form of vitamin A, is the drug of last resort for the treatment of severe acne. Depression, suicidal ideation, and psychosis are among the most well-documented psychiatric side effects. Here, we report a case of isotretinoin-induced psychosis, which was diagnosed as delusional disorder somatic subtype, in a young male in the absence of any prodromal symptoms, previous psychiatric history, or family history of mental illness. The onset of psychosis was in the context of a dosage increase from 40 mg/day to 80 mg/day. Isotretinoin was discontinued, and the patient showed improvement on low-dose quetiapine.